GANGGUAN MENTAL EMOSIONAL REMAJA SEKOLAH MENENGAH PERTAMA DI ERA MEDIA SOSIAL - Wuryaningsih, Emi Wuri; Lusmilasari, Lely; Haryanti, Fitri; Wahyuni, Budi; Erlando, Robby Prihadi Aulia (LPPM UNIVERSITAS MUHAMMADIYAH GOMBONG, 2024)
Adolescence is a transition period from childhood to adulthood. The post-Covid-19 pandemic has brought significant changes to the lifestyle of adolescents in Indonesia, especially in the use of social media. New habits of adolescents include playing online games and communicating through social media. This study aimed to identify emotional and mental problems in adolescents amidst the massive use of social media among adolescents. The design of this study was cross-sectional. The participants involved were 417 junior high school students aged (12-15) years. SDQ was used to identify students' emotional mentality. Participants who filled out the SDQ were 45.3% female and 54.7% male students with an average age of 13.64 years; ±0.17. Almost all students use social media, such as WhatsApp (98.8%), TikTok (92.6%), and Instagram (79.1%). Emotional problems (22.1%), conduct problems (62.4%), peer problems (27.3%), and hyperactivity (9.6%) showed abnormal categories. This finding aligns with the abnormal prosocial ability of (54.4%). Overall, participants in the normal category were 32.4%. The screening results showed that the emotional and mental well-being of junior high school adolescents was quite concerning and required follow-up to improve students' prosocial abilities. Assessments with other instruments are needed for comparison.